A decade of rising alcoholic liver disease hospital admissions and deaths in Irish hospitals, 2007–2016: a retrospective cross-sectional analysis. Issue 6 (4th January 2022) - Armstrong, Paul R.; Ring, Éabha; MacNicholas, Ross
Abstract : Background: Alcoholic liver disease (ALD) is a major cause of both liver cirrhosis and hepatocellular carcinoma (HCC) in Ireland. Aims: The aim of the study was to identify the epidemiological profile, temporal trends, development of complications and mortality arising from inpatient care episodes linked to ALD in Ireland from 2007 to 2016. Methods: This was a national retrospective study that analysed data on patient discharges from hospitals across Ireland. The Hospital Inpatient Enquiry System was used to gather this data. The main outcome measures were the number of hospital discharges for patients with ALD or HCC, also expressed per 100 000 population, the mortality rate associated with ALD and the prevalence of complications associated with ALD. Results: A total of 33 794 hospital discharges were examined. There was a 38% increase in hospital discharges and 300% increase in HCC coding for patients with ALD between 2006 and 2016. There were 73 hospital discharges with ALD per 100 000 population in 2016. That year, 40 482 bed days were required for inpatient management equating to 120 beds per day. Deaths from ALD rose by 29% over the 10-year period. Cirrhosis was diagnosed in 57% and 24% had ascites. Mortality was 9.8% rising to 16% with variceal bleeding and 42% with acute kidney injury. Only 31% were under the care of a gastroenterologist or hepatologist. Conclusion: Ireland is seeing a rise in ALD-related hospital admissions and deaths, including HCC which increased three-fold. ALD is a preventable disease, and public health interventions are of proven benefit and required to reverse this trend.